2005
DOI: 10.1089/jpm.2005.8.280
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Prognosis to Terminally Ill Patients: Attitudes and Practices Among French Physicians

Abstract: Disclosure of the prognosis to terminally ill patients is still far from systematic in France. Further research is needed to better understand the motivations of French physicians' disclosure practices, which are probably culturally shaped.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…A questionnaire was developed based on a review of the literature (2,3,8,9) and discussions among the authors. Content validity was assessed by full agreement of the authors, and face validity was confirmed by a pilot test of 20 potential participants.…”
Section: Methodsmentioning
confidence: 99%
“…A questionnaire was developed based on a review of the literature (2,3,8,9) and discussions among the authors. Content validity was assessed by full agreement of the authors, and face validity was confirmed by a pilot test of 20 potential participants.…”
Section: Methodsmentioning
confidence: 99%
“…Post-hoc evaluation indicated strong internal consistency construct validity for each of the major subsections, in particular the 27 attitude items and the four clinical scenarios that were the basis for the clinical behavior summary scores. Compared with previously published survey tools [40,[61][62][63][64]80] this tool provided substantially greater detail regarding attitudes and self-reported clinical behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous surveys of oncologists' attitudes and practices regarding disclosure have indicated that oncologists vary substantially in the disclosure practices [55,[61][62][63][64][65][66][67]; further, and the degree of disclosure with any one patient is highly influenced by individual factors [65][66][67][68]. Overall, survey data indicate that oncologists from Western countries are more disclosive than those practicing in nonWestern countries [61], and that other factors such as sex [61], age [61], training in the communication of bad news [4,[69][70][71][72], and frequent requests from family members for non-disclosure [40,55,73] may affect attitudes and actual clinical behaviors.…”
mentioning
confidence: 99%
“…Christakis, et al found in their study on self-reported practice regarding prognostication 20 that many physicians try to avoid prognostication and 43.7% reported that they usually wait to be asked by a patient. Peretti-Watel, et al 26 reported that one physician in eight opted for systematic concealment of prognosis and two-thirds expressed a preference for disclosing the prognosis to competent terminally ill patients only at the patient's request. This is comparable to our study where 70.5% and 53.3% of physicians discuss life expectancy and incurability, respectively, at the patient's request and 11.3% and 4.6%, respectively, do not discuss life expectancy and incurability.…”
Section: Discussionmentioning
confidence: 99%
“…The few studies conducted on the latter subject focus mainly on prognostic disclosure. [19][20][21]25,26 Several studies also point out the importance of the involvement of patients' relatives in the information process. [27][28][29] Although most patients prefer their relatives to be involved, it is also important to respect patients' autonomy and to obtain their consent prior to disclosing information to their relatives.…”
Section: Introductionmentioning
confidence: 99%